2010
DOI: 10.1149/1.3276059
|View full text |Cite
|
Sign up to set email alerts
|

1H-Benzotriazole Incorporated Pad for Chemical Mechanical Planarization of Copper

Abstract: Chemical mechanical polishing ͑CMP͒ pads are generally designed to play a passive role in terms of chemical reactions that occur on the surface to be polished. For copper CMP, a pad that is capable of initiating and controlling various chemical reactions on the copper surface can bring another dimension of flexibility to the CMP process. This work investigates such a model pad for its potential applications in copper CMP. More specifically, the physical and chemical properties of a polyurethane pad containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The polishing properties of CMP pads are both intrinsic and extrinsic functions of the polymer type used and the resulting foam morphology [5,[12][13][14][15][16][17]. Oliver et al [12] have shown that several factors contribute to the modification of pad properties.…”
Section: A Chemical Mechanical Polishing (Cmp) Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The polishing properties of CMP pads are both intrinsic and extrinsic functions of the polymer type used and the resulting foam morphology [5,[12][13][14][15][16][17]. Oliver et al [12] have shown that several factors contribute to the modification of pad properties.…”
Section: A Chemical Mechanical Polishing (Cmp) Processmentioning
confidence: 99%
“…Contact area has been shown to depend on surface morphology, which in turn depends on pore size, pore size distribution and material properties [30,31]. Therefore, it is desirable to manufacture pads with controlled porosity and pore size to increase pad-wafer contact area as well as to maintain pad-to-pad polishing consistency [15].…”
Section: A Chemical Mechanical Polishing (Cmp) Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in defects and surface topography may be a result of galvanic corrosion/pitting, micro-scratching, particle contamination, line dishing, or edge-over-erosion, among others. [5][6][7][8][9][10] Modulating the chemical and physical stress at the Cu/slurry/pad interface will be key to limiting post-CMP defects and is controlled by selectively altering slurry chemistry. A typical Cu CMP slurry is a colloidal dispersion of nanoparticles coupled with chemical components including: complexing agents, corrosion inhibitors (passivating agents), oxidizers, rheological modifiers (i.e.…”
mentioning
confidence: 99%
“…The key components in CMP process involve wafer, slurry and pad. 15,16 In order to obtain higher removal rate of SiC wafer and ultrasmooth surface, a novel photo-catalyst incorporated pad is developed z E-mail: zhouyanbebe@126.com; pangs@tsinghua.edu.cn for polishing of on-axis Si-face SiC wafer in the paper. TiO 2 could be release holes and electrons under UV light.…”
mentioning
confidence: 99%